2015
DOI: 10.3109/13625187.2015.1031885
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences and providers’ observations on pain during intrauterine device insertion

Abstract: ObjectiveTo determine women's (patients') experiences of intrauterine device (IUD) insertion under our current practice and the extent to which these agreed with the observations of the health professionals (providers) who had performed the IUD insertion procedures. MethodQuestionnaires were used to collect information on women's experiences of the IUD insertion procedure from both patients and providers in a sexual and reproductive health service. ResultsOverall response rates were high (77%, 284 responses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…However, the HCPs completed their assessments retrospectively and would have had difficulty monitoring the patients' facial expressions whilst performing the insertion which could inhibit the clinicians' interpretation of and degree of empathy with the patients' pain (Botvinick et al 2005). Similar results were found in studies on pain in relation to IUC insertion undertaken by Akintomide et al (2015) via questionnaire in the UK and in the Iranian study by HajiEsmaeilou et al (2014) using a VAS. Such concordant findings from three different continents reinforce the assumption that underestimation of patient's pain is a universal problem.…”
Section: Trustmentioning
confidence: 53%
See 1 more Smart Citation
“…However, the HCPs completed their assessments retrospectively and would have had difficulty monitoring the patients' facial expressions whilst performing the insertion which could inhibit the clinicians' interpretation of and degree of empathy with the patients' pain (Botvinick et al 2005). Similar results were found in studies on pain in relation to IUC insertion undertaken by Akintomide et al (2015) via questionnaire in the UK and in the Iranian study by HajiEsmaeilou et al (2014) using a VAS. Such concordant findings from three different continents reinforce the assumption that underestimation of patient's pain is a universal problem.…”
Section: Trustmentioning
confidence: 53%
“…Similar results were found in studies on pain in relation to IUC insertion undertaken by Akintomide et al . () via questionnaire in the UK and in the Iranian study by HajiEsmaeilou et al . () using a VAS.…”
Section: Resultsmentioning
confidence: 99%
“…The perception of pain is influenced by the patient's relationship with the physician [25][26][27]. One of the risk factors associated with increased pain intensity with gynecological procedures is the prediction a high level of pain prior to the procedure [28,29]. There is still no explanation for this finding in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Another major contributor to pain at IUD insertion was anxiety. It is well known that higher anxiety levels may increase perceived pain to levels worse than the pain actually is [27][28][29]. A previous study found that women who were more anxious and who anticipated that the procedure would be painful recalled later that it was a painful experience even if they had not experienced any pain during the procedure [4].…”
Section: Dıscussionmentioning
confidence: 99%